Effectiveness of Detention by Public Prosecutors Against Perpetrators of Criminal Acts - Agus Salim; Achmad Faishal; Suprapto Suprapto (International Forum of Researchers and Lecturers, 2026)
Detention is one of the most coercive measures in the criminal justice process and is intended to ensure the effectiveness of criminal proceedings. In many legal systems, public prosecutors are granted authority to order detention against suspects or defendants under specific legal requirements. However, the practical effectiveness of detention by public prosecutors in achieving procedural objectives and safeguarding legal rights remains a subject of debate. This study aims to examine the effectiveness of detention carried out by public prosecutors against perpetrators of criminal acts, focusing on its legal basis, implementation, and impact on the criminal justice process. Using a normative juridical approach supported by qualitative analysis of legislation, legal doctrines, and relevant case studies, this research evaluates whether prosecutorial detention fulfills principles of legality, necessity, proportionality, and human rights protection. The findings indicate that while detention by public prosecutors can enhance procedural efficiency and prevent obstruction of justice, its effectiveness is often constrained by inconsistencies in application, weak judicial oversight, and potential risks of arbitrary detention. This study concludes that strengthening legal safeguards, standardizing detention criteria, and enhancing accountability mechanisms are essential to ensure that detention by public prosecutors remains both effective and compliant with the rule of law.